Foreign Reserves or Interest Rates? Exchange Rate Determinants and Risk Management in Indonesia Instant Noodle Industry - Kayla Nur Puji Anisa, Zahara; Puspitasari, Diana (Inovasi Analisis Data, 2025)
Purpose: The focus of this research is on analyzing the relative role of external buffers and policy tools in determining exchange rate dynamics and assessing their implications for risk management, particularly in import-dependent manufacturing sectors. The study attempts to determine the main macroeconomic factor that influences currency dynamics by contrasting the impacts of foreign exchange reserves and policy interest rates. Method: The research is quantitative in nature, based on the analysis of secondary macro-economic data and an integrated structural modeling framework. Several macroeconomic factors are jointly considered to account for their direct influence on exchange rates, whilst focusing more on the strength of the effect, variance explanation, or predictive capability than on stand-alone significance. Findings: The findings suggest that in terms of the effect on the exchange rate, both foreign exchange reserves and the policy interest rate are consistent with their directional movements, implying stabilizing roles in the macroeconomic system. But on the whole, our results indicate that exchange rate behavior depends on a combination of monetary conditions, external buffers, and global commodity-driven pressures as opposed to one major policy instrument. Novelty: This paper is a novel contribution to the literature by taking a comparative approach on both external and monetary policy mechanisms in an integrated framework, with a clear focus of exchange rate dynamics hinged upon the risk factors and import-dependent sectors. Implications: The results have implications for policy in the configuration of symmetric exchange rate stabilization strategies, and guiding tools that are useful for real firms to navigate currency exposure in a context of volatility in the global economy.